The Interaction of Sex and Power Base on Perceptions of Managerial Effectiveness - Wiley, Mary Glenn; Eskilson, Arlene (Academy of Management Journal, 1982)
This article presents information on a study which examined the interaction of sex and power base using a limited sample of managers. It reveals that characteristics associated with successful managers are more congruent with the traits attributed to men than to women. It also examines how the use of reward and expert power is related to sex-role stereotypes. It was hypothesized that the use of expert power by women would require sex-role inconsistent claims of expertise and competence. It discusses the limitations of the study. The research showed that similar strategies by men and women does not mean there will be an equivalent evaluation of their performance.